Gambaran Tingkat Depresi Pada Lansia yang Tinggal di Panti Griya Sehat Bahagia Palur Karanganyar - Mahendra, Dwi Darmawan; , Abi Muhlisin, SKM, M.Kep (2016)
Elderly who has been living in nursing home is never think before it. The reduce of physically and not live with family members for long time can caused depression of elderly. The results of pre study was known the reason elderly was send by family members, do not have a family member or initiative elderly self made elderly depression. The objective was Descriptive of elderly depression level at an griya sehat bahagia nursing home of palur karanganyar. The sample was all of member at griya sehat bahagia nursing home count 55 persons, taking sample use total sampling technique. Instrument research use geriatric depression scale-15. Questionnaire. Data analysis use frequency analysis with count sample and percentage. The results of study that 49.1 % age of respondents among 60-74 years old, 63.6 % respondents still with married status, 60 % respondents with Christians religion, 92,8 % respondents have been living more than 2 years, 87.3 % reason respondents live in nursing home by advice of their family. As many as 94.5 % respondents suffer depression, with age of respondents above 60 years old, respondents with married status majority suffer depression.